OPEC at a glance - Organization of Petroleum Exporting Countries (Vienna, Austria : Organization of the Petroleum Exporting Countries, 1988)
This guide provides a details information about the composition, structure and administrative policies of the organisation of petroleum exporting countries (OPEC)., including it aims and objective for the betterment of the member countries.
asm 06/03/19
Loans
Keywords: Petroleum industry and trade; Organization of Petroleum Exporting Countries; Energy; OPEC